‏Enhancing Health Security in Saudi Arabia: Strategies for Preparedness and Response to Epidemics and Biological Threats - Ismail, Moamen Abdelfadil; Alharbi, Ahlam Ibrahim; Alharbi, Ahmed Eid Mohammed; Alotaibi, Aljawharah mohammed; ALGHUBAINI, AHMAD ALI; ALAZMI, NAIF NAWAF; Alazmi, Salman Saad; Asiri, Samiyah Mohammed Hassan; Mudarbish, Abdulrahman Ibrahem Yahya; hashmi, Mohammed saleh saleh; Mudarbish, Nujud Ibrahem Yahya (Journal of Ecohumanism, 2024)
Background: Saudi Arabia has made significant progress in enhancing its health security through robust preparedness and response mechanisms to address epidemics and biological threats. Given its strategic location, dense population centers, and the annual influx of pilgrims for Hajj and Umrah, the country faces unique challenges in disease prevention and control. The COVID-19 pandemic underscored the importance of resilient healthcare systems, rapid response frameworks, and digital health technologies. This study evaluates Saudi Arabia’s health security strategies, focusing on preparedness, public awareness, and resource availability. Methods: A mixed-methods research design was employed, combining quantitative surveys with qualitative expert interviews. The study involved 250 survey respondents and 50 interviews with public health officials, healthcare professionals, and academic researchers. Data were collected through structured questionnaires, epidemiological trend analysis, in-depth interviews, and policy document reviews. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were thematically coded using NVivo software. Results: The findings revealed that 85% of participants had moderate to high awareness of epidemic preparedness strategies, though 15% reported low awareness. Half of the respondents expressed confidence in the health system’s response capabilities, while 25% were not confident. Resource availability was inconsistent, with 50% reporting occasional shortages. Key challenges included insufficient public awareness (35%), lack of medical resources (25%), and coordination gaps (20%). Suggested improvements included more public awareness campaigns (45%) and increased healthcare funding (25%). Conclusion: Saudi Arabia has established a strong foundation for health security, but gaps remain in public awareness, resource allocation, and inter-sectoral coordination. Strengthening public education, ensuring consistent medical supplies, and enhancing collaboration between stakeholders are critical for future preparedness. The study highlights the need for continuous improvement and alignment with global health security standards to mitigate the impact of epidemics and biological threats effectively.